CD93 blockade promotes effector T-cell infiltration and facilitates adoptive cell therapy in solid tumors - Yi Sun; Eduardo Davila; YuJie Guo; Richard D Schulick; Elliott Yee; Yuki Fujiwara; Kaitlyn Dickinson; Zhiwei Sun; Junyi Hu; Yuwen Zhu (Journal for ImmunoTherapy of Cancer)
Background Adaptive cellular therapy (ACT), particularly chimeric antigen receptor (CAR)-T cell therapy, has been successful in the treatment of hemopoietic malignancies. However, poor trafficking of administered effector T cells to the tumor poses a great hurdle for this otherwise powerful therapeutic approach in solid cancers. Our previous study revealed that targeting CD93 normalizes tumor vascular functions to improve immune checkpoint blockade therapy. The objective of this study is to evaluate whether CD93 blockade improves ACT in solid cancers.Methods Monoclonal antibodies (mAbs) against CD93 or IGFBP7 were administered in implanted mouse melanoma models to assess the effect of CD93 blockade on ACT. Different sources of effector T cells were used, including pre-activated CD8+OT-1, pmel-1 transgenic T cells, and CAR-T cells. Rip-OVA and Rip-TAG-OVA transgenic mice were used to evaluate the selective impact of CD93 blockade on effector T-cell infiltration in tumors. For mechanistic studies, vascular maturation was determined by immunofluorescent staining and flow cytometry was performed to examine tumor-infiltrating T lymphocytes. Neutralizing mAbs against adhesion molecules ICAM1 and VCAM1 were infused to assess their involvement.Results Blockade of the CD93 pathway increases the expression of adhesion molecules on tumor vasculature to improve effector T-cell infiltration and function. T-cell transfer and CD93 blockade synergistically improve tumor vascular maturation, as well as inhibit tumor progression. Anti-CD93 selectively promotes effector T-cell infiltration in a tumorous setting where the CD93 pathway is upregulated. In a solid mouse tumor model, blockade of the CD93 pathway improves CAR-T therapy.Conclusions CD93 blockade normalizes tumor vasculature leading to improved effector T-cell infiltration and function in solid cancers. Our study advocates the application of CD93 blockade for ACT in solid cancers.